2010
DOI: 10.1007/s10681-010-0331-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of tomato SSR markers from anchored BAC clones of chromosome 12 and their application for genetic diversity analysis and linkage mapping

Abstract: In this study, we developed a total of 37 simple sequence repeat (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…GD analysis is important for collections, conservation, and sustainable utilization of Genbank accessions (Suresh et al 2014). Various types of DNA markers studies have been carried out to estimate the GD and phylogenetic relationship among tomato genotypes (Klein-Lankhorst et al 1991;Kwon et al 2009;Geethanjali et al 2011). Various methods have been used for surveying population structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GD analysis is important for collections, conservation, and sustainable utilization of Genbank accessions (Suresh et al 2014). Various types of DNA markers studies have been carried out to estimate the GD and phylogenetic relationship among tomato genotypes (Klein-Lankhorst et al 1991;Kwon et al 2009;Geethanjali et al 2011). Various methods have been used for surveying population structures.…”
Section: Discussionmentioning
confidence: 99%
“…He et al (2003) have identified 2.7 alleles per locus on average among 17 varieties and 2 parental lines of tomatoes. We used diverse tomato genetic resources preserved in the National Agrobiodiversity Center (RDA, Republic of Korea) and applied the 18 SSR markers which revealed high alleles and polymorphism based on the previous studies (Kwon et al 2009;Geethanjali et al 2010;Geethanjali et al 2011). These factors might cause relatively high average NA per locus in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the markers were minimum but are highly potential in distinguishing closely related cultivars of tomato [11]. Reported marker density based on in vivo method is relatively less on every chromosome, for example 12 th chromosome has just 37 [12]. For plant variety identification along with degree of admixture, STR is always preferred if they are in multiplex mode (for example, Basmati and non-Basmati rice can be differentiated by 8 plex/ single cocktail based PCR) [13].…”
Section: Introductionmentioning
confidence: 99%